Promoting of goodness (Amal Ma’aruf) and preventing of evil (Nahi Munkar) in the corporate culture: the roles of Muslim managers - Sarif, Suhaimi Mhd (2010)
Muslim managers have religious obligations as commanded by Allah, that is to serve as the servant of Allah (‘abd Allah) and vicegerent of Allah (khalifah Allah fil Ard). One of them is to promote goodness (‘amal ma’aruf) and to prevent evil (nahi munkar). In the modern managerial paradigm, managers are expected to get things done in organizations through their fellow colleagues efficiently and effectively. Generally, Muslim managers are aware of their religious obligations. This paper investigates the perceptions of 30 Australian Muslim managers using Al Qurtubi Model toward operationalizing the promotion of goodness (‘amal ma’aruf) and prevention of evil (nahi munkar) in their companies’ corporate culture. The study used mixed methods, both quantitative and qualitative, to generate rich data for analysis. The results showed that the Australian Muslim Managers were aware about their religious obligations to practice the promotion of goodness and the prevention of evil. However, the results were not conclusive considering constraints on sample size of the study (survey, n=110 and interview, n=30). The study proposed that future research use case study method to understand the operationalization of the promotion of goodness (ma’aruf) and the prevention of evil (munkar) in Australian managerial contexts.